Positive electrode material and preparation method and application thereof

By calculating carbon nitride and doping with fluorine, the existing cathode materials have been solved, and the electrochemical performance of sodium ion batteries has been improved, and high capacity and high voltage are achieved. Application of the platform.

CN119208575APending Publication Date: 2024-12-27ZHUHAI NAYI NEW ENERGY TECH CO LTD
View PDF 0 Cites 6 Cited by

Patent Information

Application Number
CN202411468030.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing polyanionic positive electrode materials have poor capacity and low energy density in sodium ion batteries, resulting in less competitiveness in small dynamic scenarios, and the low electronic conductivity of manganese and the Jiang Taylor effect during charging and discharging limit it. Capacity playback.

Method used

Carbon nitride coating and fluorine doping by focusing sodium ferromanganese phosphate, improving its electronic conductivity and structural stability, and preparing carbon nitride coated fluorine-doped sodium ferromanganese phosphate (NaaFe3-bMnb(PO4)) -x)2F4xP2O7/C3N4) is a cathode material, and a simple synthesis process and low-cost raw materials are used.

Benefits of technology

The voltage platform and capacity of sodium ion batteries have been improved. The first discharge specific capacity reaches more than 99mAh/g, and the average discharge voltage platform can reach more than 3.27V, which significantly improves the electrochemical performance of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005093936940000081
    Figure BDA0005093936940000081
Patent Text Reader

Abstract

The invention belongs to the field of sodium ion batteries, and particularly discloses a positive electrode material and a preparation method and application thereof. The positive electrode material is carbon nitride coated fluorine-doped pyrophosphate sodium manganese iron phosphate, the chemical formula of the positive electrode material is NaaFe3-bMnb (PO4-x) 2F4xP2O7 / C3N4, a is larger than or equal to 3.95 and smaller than or equal to 4.1, b is larger than or equal to 0.3 and smaller than or equal to 2.4, and x is larger than or equal to 0.005 and smaller than or equal to 0.05. The sodium ferromanganese pyrophosphate is subjected to fluorine doping and carbon nitride coating, so that the electronic conductivity and the structural stability of the sodium ferromanganese pyrophosphate can be improved, the capacity of the sodium ferromanganese pyrophosphate can be well exerted, and the capacity and the voltage platform of the sodium-ion battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of sodium ion batteries, and in particular relates to a positive electrode material and a preparation method and application thereof. Background Art

[0002] Sodium is abundant in the earth's crust, widely distributed, and simple to produce, providing a raw material guarantee for the development of low-cost sodium-ion batteries. Compared with lithium ions, sodium ions have a larger ionic radius, so sodium ions have better rate performance. In addition, sodium and aluminum are not prone to alloying reactions, and both the positive and negative current collectors of sodium-ion batteries can use relatively low-cost aluminum foil. The production process of sodium-ion batteries is similar to that of lithium-ion batteries, making the industrial development of sodium-ion batteries compatible with existing lithium-ion battery production equipment, reducing technical bottlenecks and further reducing production costs. Therefore, sodium-ion batteries, as low-cost and high-safety products, have very broad application prospects.

[0003] As sodium storage materials for sodium ion batteries, polyanion compounds are one of the most promising cathode materials for the development of low-cost sodium ion batteries due to their simple synthesis methods, high structural stability, and easy large-scale production. The research on their sodium storage performance has very important practical significance for promoting the industrialization of sodium ion batteries. At present, polyanion cathode materials still face many challenges in practical applications. For example, the theoretical capacity of sodium iron pyrophosphate material is 129mAh / g, and the average voltage is 3.0V. Although its capacity is high, its low voltage leads to low energy density, which is far behind layered oxides and Prussian blue sodium ion cathode materials, and its competitiveness is relatively low in small power scenarios. Due to the presence of manganese, ferromanganese pyrophosphate increases the voltage platform and can provide higher energy at the same capacity, which has great development potential. However, the low electronic conductivity of manganese and the Jan-Taylor effect in the charge and discharge process also limit its capacity, which ultimately leads to poor capacity performance. Summary of the invention

[0004] In view of the problem of poor capacity of the sodium ferromanganese pyrophosphate system involved in the above-mentioned prior art, the present invention will provide a positive electrode material and its preparation method and application. The positive electrode material of the present invention is fluorine-doped sodium ferromanganese pyrophosphate coated with carbon nitride. In the present invention, the sodium ferromanganese pyrophosphate is fluorine-doped and carbon nitride-coated, which can improve the electronic conductivity and structural stability of the sodium ferromanganese pyrophosphate, so that its capacity can be better exerted. In addition, the synthesis process of the positive electrode material is simple and low-cost, which further promotes the application of pyrophosphate materials in sodium ion batteries.

[0005] To achieve the above purpose, the following technical solutions are specifically included:

[0006] On the one hand, the present invention provides a positive electrode material, which is a carbon nitride-coated fluorine-doped sodium manganese iron pyrophosphate, whose chemical formula is Na a Fe 3-b Mn b (PO 4-x )2F 4x P2O7 / C3N4, where 3.95≤a≤4.1, 0.3≤b≤2.4, 0.005≤x≤0.05.

[0007] In the chemical formula of the positive electrode material of the present invention, “ / ” represents coating, and each element is expressed in terms of molar ratio.

[0008] The positive electrode material of the present invention is mainly composed of sodium manganese iron pyrophosphate, and has a carbon nitride coating layer and doped elemental fluorine. The present invention performs fluorine doping and carbon nitride coating on the sodium manganese iron pyrophosphate, which can improve the electronic conductivity and structural stability of the sodium manganese iron pyrophosphate, so that its capacity can be better exerted, and the purpose of increasing the voltage platform height and capacity of the sodium ion battery can be achieved.

[0009] Preferably, the chemical formula of the positive electrode material satisfies the following relationship: 4≤a≤4.05, 1≤b≤2, 0.008≤x≤0.04.

[0010] Preferably, the chemical formula of the positive electrode material is Na 4.05 Fe 1.8 Mn 1.2 (PO 3.99 )2F 0.04 P2O7 / C3N4、Na4Fe 1.5 Mn 1.5 (PO 3.98 )2F 0.08 At least one of P2O7 / C3N4.

[0011] In another aspect, the present invention provides a method for preparing the positive electrode material, comprising the following steps:

[0012] S1: uniformly mixing a sodium source, an iron source, a manganese source, a phosphorus source, a fluorine source, a carbon source and a nitrogen source with water to obtain a mixture;

[0013] S2: grinding the mixture to obtain a slurry;

[0014] S3: spray drying the slurry to obtain a precursor;

[0015] S4: sintering the precursor in an inert gas atmosphere to obtain the positive electrode material.

[0016] The present invention improves the conductivity by coating sodium manganese iron pyrophosphate with carbon nitride, and improves the structural stability by fluorine doping, so that its capacity can be better exerted. In the preparation method of the present invention, generally only one step of high temperature treatment is used at the end, the overall preparation process is simple, and the production cycle is short. In addition, the raw materials used in the preparation are all commercially available, which greatly reduces energy consumption and cost.

[0017] Preferably, in step S1, the sodium source includes at least one of sodium carbonate, sodium bicarbonate, sodium dihydrogen phosphate, disodium hydrogen phosphate, and sodium pyrophosphate.

[0018] Preferably, in step S1, the iron source includes at least one of ferric phosphate, ferrous oxalate and ferric nitrate.

[0019] Preferably, in step S1, the manganese source includes at least one of manganese carbonate, manganese oxalate, manganese acetate and manganese nitrate.

[0020] Preferably, in step S1, the phosphorus source includes at least one of ferric phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, and ammonium dihydrogen phosphate.

[0021] Preferably, in step S1, the fluorine source includes sodium fluoride.

[0022] Preferably, in step S1, the carbon and nitrogen sources include at least one of urea and melamine.

[0023] Preferably, in step S1, the carbon and nitrogen sources account for 5wt% to 15wt% of the mass of the positive electrode material.

[0024] Preferably, in step S1, the molar ratio of the sodium source, iron source, manganese source, phosphorus source and fluorine source is (3.95-4.1): (0.6-2.7): (0.3-2.4): (3.95-3.995): (0.02-0.2).

[0025] Preferably, in step S2, D50 of the slurry is ≤ 0.4 μm.

[0026] Preferably, in step S3, during the spray drying, the air inlet temperature is 180°C to 280°C, the air outlet temperature is 80°C to 120°C, and the D50 of the precursor is 5 μm to 25 μm.

[0027] The D50 involved in the present invention means: the particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50%. Its physical meaning is that particles with a particle size larger than it account for 50%, and particles with a particle size smaller than it also account for 50%.

[0028] Preferably, in step S4, the sintering comprises the following steps: heating from room temperature to 250-400° C. and keeping the temperature for 2-8 hours; then heating to 500-700° C. and keeping the temperature for 5-15 hours, and finally cooling to room temperature.

[0029] When the sintering temperature is too low, the positive electrode material will be incompletely sintered, which will significantly reduce the discharge capacity and average discharge voltage of the sodium ion battery. If it is too high, it will increase energy consumption and will not improve the electrical performance of the positive electrode material. Therefore, the sintering temperature of the present invention is selected to be 250-400°C and 500-700°C. At the above sintering temperature, the electronic conductivity and structural stability of the positive electrode material of the present invention are easier to exert its capacity, thereby achieving the purpose of improving the discharge capacity and average discharge voltage of the sodium ion battery.

[0030] Further preferably, the heating rate of the heating is each selected from 1 to 6° C. / min.

[0031] Preferably, in step S4, the inert gas includes at least one of nitrogen, argon and helium.

[0032] In addition, the present invention also provides a sodium ion battery, comprising the positive electrode material.

[0033] The positive electrode material of the present invention has high energy density and excellent cycle performance. When it is applied to the positive electrode of a sodium ion battery, the sodium ion battery has excellent electrochemical properties, such as a high voltage platform and good capacity performance. The first discharge specific capacity at a rate of 0.2C (100mAh / g) reaches more than 99mAh / g, and the average discharge voltage platform can reach more than 3.27V. The carbon nitride-coated fluorine-doped sodium manganese iron pyrophosphate of the present invention has a good application prospect as a positive electrode material for a sodium ion battery.

[0034] Compared with the prior art, the present invention has the following beneficial effects: the present invention performs fluorine doping and carbon nitride coating on sodium manganese iron pyrophosphate, which can improve the electronic conductivity and structural stability of sodium manganese iron pyrophosphate, so that its capacity can be better exerted, thereby improving the capacity and voltage platform of the sodium ion battery. DETAILED DESCRIPTION

[0035] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified.

[0036] Example 1

[0037] This embodiment provides a positive electrode material, whose chemical formula is Na 4.05 Fe 1.8 Mn1.2 (PO 3.99 )2F 0.04 P2O7 / C3N4, the preparation method of the positive electrode material comprises the following steps:

[0038] S1: Weigh 4.05 mol of sodium carbonate, 1.8 mol of iron phosphate, 1.2 mol of manganese acetate tetrahydrate, 2.19 mol of ammonium dihydrogen phosphate, 0.04 mol of sodium fluoride and 62 g of melamine (melamine accounts for 8% of the mass of the positive electrode material), add the above raw materials to 3.5 L of deionized water, and stir to obtain a mixture;

[0039] S2: The mixture is transferred to a sand mill and sand-milled until the particle size D50 reaches 0.30 μm to obtain a slurry;

[0040] S3: spray drying the slurry with an air inlet temperature of 250°C and an air outlet temperature of 90°C to obtain a precursor with a D50 of 18.5 μm;

[0041] S4: Place the precursor in a tubular furnace, and in a nitrogen atmosphere, heat it from room temperature to 300°C and keep it warm for 4 hours; then continue to heat it to 550°C and keep it warm for 10 hours, with a heating rate of 5°C / min. Finally, cool it to room temperature to obtain the positive electrode material.

[0042] Example 2

[0043] The difference between this embodiment and embodiment 1 is that the molar ratios of the sodium source, the iron source, the manganese source, the phosphorus source and the fluorine source are different.

[0044] The chemical formula of a positive electrode material in this embodiment is Na4Fe 1.5 Mn 1.5 (PO 3.98 )2F 0.08 P2O7 / C3N4, the preparation method of the positive electrode material comprises the following steps:

[0045] S1: Weigh 4 mol of sodium carbonate, 1.5 mol of iron phosphate, 1.5 mol of manganese acetate tetrahydrate, 2.48 mol of ammonium dihydrogen phosphate, 0.08 mol of sodium fluoride and 62 g of melamine, add the above raw materials to 3.5 L of deionized water, and stir to obtain a mixture;

[0046] S2: The mixture is transferred to a sand mill and sand-milled until the particle size D50 reaches 0.30 μm to obtain a slurry;

[0047] S3: spray drying the slurry with an air inlet temperature of 250°C and an air outlet temperature of 90°C to obtain a precursor with a D50 of 18.5 μm;

[0048] S4: Place the precursor in a tubular furnace, and in a nitrogen atmosphere, heat it from room temperature to 300°C and keep it warm for 4 hours; then continue to heat it to 550°C and keep it warm for 10 hours, with a heating rate of 5°C / min. Finally, cool it to room temperature to obtain the positive electrode material.

[0049] Example 3

[0050] The difference between this embodiment and embodiment 1 is that the types of substances of the sodium source, the iron source and the manganese source are different.

[0051] The chemical formula of a positive electrode material in this embodiment is Na 4.05 Fe 1.8 Mn 1.2 (PO 3.99 )2F 0.04 P2O7 / C3N4, the preparation method of the positive electrode material comprises the following steps:

[0052] S1: Weigh 4.05 mol of sodium bicarbonate, 1.8 mol of ferrous oxalate dihydrate, 1.2 mol of manganese oxalate dihydrate, 2.19 mol of ammonium dihydrogen phosphate, 0.04 mol of sodium fluoride and 62 g of melamine, add the above raw materials into 3.5 L of deionized water, and stir to obtain a mixture;

[0053] S2: The mixture is transferred to a sand mill and sand-milled until the particle size D50 reaches 0.30 μm to obtain a slurry;

[0054] S3: spray drying the slurry with an air inlet temperature of 250°C and an air outlet temperature of 90°C to obtain a precursor with a D50 of 18.5 μm;

[0055] S4: Place the precursor in a tubular furnace, and in a nitrogen atmosphere, heat it from room temperature to 300°C and keep it warm for 4 hours; then continue to heat it to 550°C and keep it warm for 10 hours, with a heating rate of 5°C / min. Finally, cool it to room temperature to obtain the positive electrode material.

[0056] Example 4

[0057] The difference between this embodiment and embodiment 1 is that the temperature and time of the sintering process are different.

[0058] This embodiment provides a positive electrode material, whose chemical formula is Na 4.05 Fe 1.8 Mn 1.2 (PO 3.99 )2F 0.04 P2O7 / C3N4, the preparation method of the positive electrode material comprises the following steps:

[0059] S1: Weigh 4.05 mol of sodium carbonate, 1.8 mol of iron phosphate, 1.2 mol of manganese acetate tetrahydrate, 2.19 mol of ammonium dihydrogen phosphate, 0.04 mol of sodium fluoride and 62 g of melamine, add the above raw materials to 3.5 L of deionized water, and stir to obtain a mixture;

[0060] S2: The mixture is transferred to a sand mill and sand-milled until the particle size D50 reaches 0.30 μm to obtain a slurry;

[0061] S3: spray drying the slurry with an air inlet temperature of 250°C and an air outlet temperature of 90°C to obtain a precursor with a D50 of 18.5 μm;

[0062] S4: Place the precursor in a tubular furnace, and in a nitrogen atmosphere, heat it from room temperature to 350°C and keep it warm for 3 hours; then continue to heat it to 600°C and keep it warm for 8 hours, with a heating rate of 5°C / min. Finally, cool it to room temperature to obtain the positive electrode material.

[0063] Comparative Example 1

[0064] The difference between this comparative example and Example 1 is that no fluorine source is added in this comparative example, that is, no fluorine doping, Na4Fe 1.8 Mn 1.2 (PO4)2P2O7 / C3N4.

[0065] Comparative Example 2

[0066] The difference between this comparative example and Example 1 is that no carbon and nitrogen source are added in this comparative example, that is, no carbonized nitrogen coating, Na 4.05 Fe 1.8 Mn 1.2 (PO 3.99 )2F 0.04 P2O7.

[0067] Comparative Example 3

[0068] The difference between this comparative example and Example 1 is that the sintering temperatures of this comparative example are 240° C. and 450° C. respectively. The specific process is as follows:

[0069] S1: Weigh 4.05 mol of sodium carbonate, 1.8 mol of iron phosphate, 1.2 mol of manganese acetate tetrahydrate, 2.19 mol of ammonium dihydrogen phosphate, 0.04 mol of sodium fluoride and 62 g of melamine, add the above raw materials to 3.5 L of deionized water, and stir to obtain a mixture;

[0070] S2: The mixture is transferred to a sand mill and sand-milled until the particle size D50 reaches 0.30 μm to obtain a slurry;

[0071] S3: spray drying the slurry with an air inlet temperature of 250°C and an air outlet temperature of 90°C to obtain a precursor with a D50 of 18.5 μm;

[0072] S4: Place the precursor in a tubular furnace, and in a nitrogen atmosphere, heat it from room temperature to 240°C and keep it warm for 4 hours; then continue to heat it to 450°C and keep it warm for 10 hours, with a heating rate of 5°C / min. Finally, cool it to room temperature to obtain the positive electrode material.

[0073] Comparative Example 4

[0074] The difference between this comparative example and Example 1 is that no fluorine source, carbon and nitrogen source are added in this comparative example, that is, no fluorine doping and carbonized nitrogen coating. The specific process is as follows:

[0075] S1: Weigh 4.05 mol of sodium carbonate, 1.8 mol of iron phosphate, 1.2 mol of manganese acetate tetrahydrate, and 2.2 mol of ammonium dihydrogen phosphate, add the above raw materials to 3.5 L of deionized water, and stir to obtain a mixture;

[0076] S2: The mixture is transferred to a sand mill and sand-milled until the particle size D50 reaches 0.30 μm to obtain a slurry;

[0077] S3: spray drying the slurry with an air inlet temperature of 250°C and an air outlet temperature of 90°C to obtain a precursor with a D50 of 18.5 μm;

[0078] S4: Place the precursor in a tubular furnace, and in a nitrogen atmosphere, heat it from room temperature to 300°C and keep it warm for 4 hours; then continue to heat it to 550°C and keep it warm for 10 hours, with a heating rate of 5°C / min. Finally, cool it to room temperature to obtain the positive electrode material.

[0079] Comparative Example 5

[0080] The difference between this comparative example and Example 1 is that in this comparative example, the mass of melamine is replaced by glucose, that is, the carbon-coated fluorine-doped sodium manganese iron pyrophosphate Na 4.05 Fe 1.8 Mn 1.2 (PO 3.99 )2F 0.04 P2O7 / C; specifically includes the following steps:

[0081] S1: Weigh 4.05 mol of sodium carbonate, 1.8 mol of ferric phosphate, 1.2 mol of manganese acetate tetrahydrate, 2.19 mol of ammonium dihydrogen phosphate, 0.04 mol of sodium fluoride and 62 g of glucose, add the above raw materials to 3.5 L of deionized water, and stir to obtain a mixture;

[0082] S2: The mixture is transferred to a sand mill and sand-milled until the particle size D50 reaches 0.30 μm to obtain a slurry;

[0083] S3: spray drying the slurry with an air inlet temperature of 250°C and an air outlet temperature of 90°C to obtain a precursor with a D50 of 18.5 μm;

[0084] S4: Place the precursor in a tubular furnace, and in a nitrogen atmosphere, heat it from room temperature to 300°C and keep it warm for 4 hours; then continue to heat it to 550°C and keep it warm for 10 hours, with a heating rate of 5°C / min. Finally, cool it to room temperature to obtain the positive electrode material.

[0085] Application examples:

[0086] (1) Preparation of positive electrode sheets for sodium ion batteries:

[0087] The positive electrode materials prepared in each embodiment and comparative example were mixed with conductive carbon (Super P) and binder polyvinylidene fluoride (PVDF) in a mass ratio of 7:2:1, and after grinding, an appropriate amount of 1-methyl-2-pyrrolidone (NMP) solvent was added, and the mixture was placed in a homogenizer and vibrated for 10 minutes, and the slurry was evenly coated on the carbon-coated aluminum foil. After drying, the aluminum foil coated with the black slurry was punched into a circular electrode sheet with a diameter of 14 mm using a slicer, and then a tablet press was used to apply a certain pressure to the electrode sheet for tableting. Finally, the electrode sheet was placed in a vacuum oven and vacuum dried at 120° C. for 12 hours to obtain a positive electrode sheet for a sodium ion battery;

[0088] (2) Preparation of sodium ion batteries

[0089] The prepared sodium ion battery positive electrode was used as the working electrode, metallic sodium was used as the counter electrode, and 1 mol / L NaClO4 / PC:EMC:FEC (49:49:2) organic electrolyte was used to assemble button cells in a glove box filled with argon atmosphere;

[0090] (3) Electrical performance test

[0091] The electrochemical performance of the prepared sodium ion battery was tested by conventional methods in the art. The test voltage was 2.0-4.3V, the rate was 0.2C, the first charge and discharge specific capacity and the average discharge voltage were measured at 20mA. The test results are shown in Table 1.

[0092] Table 1

[0093]

[0094] It can be seen from the above embodiments that the sodium ion battery prepared by the carbon nitride-coated fluorine-doped sodium manganese iron pyrophosphate positive electrode material of the present invention has a first discharge specific capacity greater than 99 mAh / g at 20 mA, and a first discharge average voltage greater than 3.27 V at 20 mA, and the battery capacity and voltage platform are high.

[0095] It can be seen from the comparison between Example 1 and Comparative Examples 1-2 that the fluorine-doped and carbonitrided nitrogen-coated positive electrode material can significantly improve the discharge specific capacity and average discharge voltage of the sodium ion battery.

[0096] It can be seen from Examples 1, 4 and Comparative Example 3 that when the sintering temperature is too low, the positive electrode material will be incompletely sintered, which will significantly reduce the discharge specific capacity and average discharge voltage of the sodium ion battery. If it is too high, it will increase energy consumption and will not improve the electrical performance of the positive electrode material much. Therefore, the sintering temperature of the present invention is selected to be 250-400°C and 500-700°C. At the above sintering temperature, the electronic conductivity and structural stability of the positive electrode material of the present invention are easier to exert its capacity, thereby achieving the purpose of improving the discharge specific capacity and average discharge voltage of the sodium ion battery.

[0097] It can be seen from Examples 1-3 that the types of sodium source, iron source, manganese source and the molar ratio of sodium source, iron source, manganese source, phosphorus source and fluorine source have little effect on the discharge specific capacity and average discharge voltage of the sodium ion battery. Therefore, the carbon nitride-coated fluorine-doped sodium manganese iron pyrophosphate of the present invention has a chemical formula of Na a Fe 3-b Mn b (PO 4-x )2F 4x P2O7 / C3N4, where 3.95≤a≤4.1, 0.3≤b≤2.4, 0.005≤x≤0.05, has good discharge specific capacity and discharge average voltage.

[0098] It can be seen from Example 1 and Comparative Examples 4-5 that fluorine doping and nitrogen carbide coating of the positive electrode material can significantly improve the discharge specific capacity of the sodium ion battery.

[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A positive electrode material, characterized in that: It is a carbon nitride coated fluorine-doped sodium manganese iron pyrophosphate, and its chemical formula is Na a Fe 3-b Mn b (PO 4-x )2F 4x P2O7 / C3N4, where 3.95≤a≤4.1, 0.3≤b≤2.4, 0.005≤x≤0.

05.

2. The positive electrode material according to claim 1, characterized in that The chemical formula of the positive electrode material satisfies the following relationship: 4≤a≤4.05, 1≤b≤2, 0.008≤x≤0.

04.

3. The positive electrode material according to claim 1, characterized in that The chemical formula of the positive electrode material is Na 4.05 Fe 1.8 Mn 1.2 (PO 3.99 )2F 0.04 P2O7 / C3N4、Na4Fe 1.5 Mn 1.5 (PO 3.98 )2F 0.08 At least one of P2O7 / C3N4.

4. A method for preparing the positive electrode material according to any one of claims 1 to 3, characterized in that: The steps include: S1: uniformly mixing a sodium source, an iron source, a manganese source, a phosphorus source, a fluorine source, a carbon source and a nitrogen source with water to obtain a mixture; S2: grinding the mixture to obtain a slurry; S3: spray drying the slurry to obtain a precursor; S4: sintering the precursor in an inert gas atmosphere to obtain the positive electrode material.

5. The method for preparing the positive electrode material according to claim 4, characterized in that: In step S4, the sintering includes the following steps: heating from room temperature to 250-400° C. and keeping the temperature for 2-8 hours; then heating to 500-700° C. and keeping the temperature for 5-15 hours, and finally cooling to room temperature.

6. The method for preparing the positive electrode material according to claim 5, characterized in that: The heating rates of the heating are each selected from 1 to 6° C. / min.

7. The method for preparing the positive electrode material according to claim 4, characterized in that: Include at least one of the following: In step S1, the sodium source includes at least one of sodium carbonate, sodium bicarbonate, sodium dihydrogen phosphate, disodium hydrogen phosphate, and sodium pyrophosphate; In step S1, the iron source includes at least one of ferric phosphate, ferrous oxalate, and ferric nitrate; In step S1, the manganese source includes at least one of manganese carbonate, manganese oxalate, manganese acetate, and manganese nitrate; In step S1, the phosphorus source includes at least one of ferric phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, and ammonium dihydrogen phosphate; In step S1, the fluorine source includes sodium fluoride; In step S1, the carbon and nitrogen sources include at least one of urea and melamine.

8. The method for preparing the positive electrode material according to claim 4, characterized in that: In step S1, the carbon and nitrogen sources account for 5wt% to 15wt% of the mass of the positive electrode material.

9. The method for preparing the positive electrode material according to claim 4, characterized in that: In step S2, the D50 of the slurry is ≤0.4 μm; in step S3, during the spray drying, the air inlet temperature is 180°C to 280°C, the air outlet temperature is 80°C to 120°C, and the D50 of the precursor is 5 μm to 25 μm.

10. A sodium ion battery, characterized in that: The positive electrode material comprises the positive electrode material according to any one of claims 1 to 3.

Citation Information

Cited By

  • NFPP nanosheet coated layered oxide positive electrode material and preparation method and application thereof

    CN120895605A

  • Nfpp nanosheet-coated layered oxide positive electrode material and preparation method and application thereof

    CN120895605B

  • Nitrogen-doped carbon-coated mixed sodium ferric pyrophosphate polyanion positive electrode material and preparation method thereof

    CN121149203A

  • High-magnification ferric sodium pyrophosphate positive electrode material and preparation method thereof

    CN121202095A

  • Carbon nitride coated sodium manganese phosphate pyrophosphate-based positive electrode material, preparation method and application

    CN121790374A